Otatea nayeeri (Poaceae: Bambusoideae: Bambuseae: Guaduinae), a new species endemic to Nayarit, Mexico - Ruiz-Sanchez, Eduardo; Castro-Castro, Arturo (Phytotaxa, 2016)
Otatea is the most diverse genus of Guaduinae in Mexico, with 10 described species mostly inhabiting tropical dry forest. Here, with the description of Otatea nayeeri, the number of species increases to 11. Morphologically, O. nayeeri is similar to O. reynosoana and O. transvolcanica but differs in having thin-papery and deciduous culm leaves, oral setae absent in culm leaves, developing erect and reflexed culm leaf blades, three subequal branches per node and smaller foliage leaf blades without fimbriae. A comparative table of vegetative characters, an illustration and photographs are also provided.